Application of tofu dregs as an alternative feed for tilapia (Oreochromis niloticus) cultivation in rapid water ponds - Prameswari, Aurel Sasqia; Permatasari, Sheny; Kurniawan, Angga; Wiyoto, (JURNAL MINA SAINS, 2024)
The leading cause of the high price of fish feed is the increase in the price of raw feed material. One way to reduce the dependence on relatively expensive raw materials is to utilize alternative raw materials, such as tofu dregs. This research was conducted to evaluate the influence of including tofu dregs in feed on the technical coefficient of tilapia cultivation. This study used a completely randomized design (CRD) with four treatments and three replicates: AP8020 (80% tofu dregs + 20% pellets), AP6040 (60% tofu dregs + 40% pellets), AP4060 (40% tofu dregs + 60% pellets), and K (100% pellets as a control). Duncan's further test was conducted to determine the best treatment between treatments. The results showed that mixing 40% tofu dregs with 60% tilapia pellets (AP4060) could increase the increase in Absolute Length, Absolute Weight Gain, Specific Weight Growth Rate, and feed conversion ratio by 15.80 cm, 291.27 gr, 5.74%, and 0.71, respectively. The conclusion of the study shows that mixing tofu dregs and pellets affects the technical coefficient of tilapia growth compared to the control (100% pellets) in the best treatment AP4060 (40% tofu dregs + 60% pellets).